Study of Glycated Hemoglobin (Hba1C) Levels in Iraqi Pregnant Women with Non-Diabetic Iron Deficiency Anemia - Ali Ibrahim Mohammed AL-Samawi; Hassnien S. Al-Hashemi (World Journal of Experimental Biosciences, 2017)
The objective of the present study was to determine whether the Glycosylated hemoglobin (HbA1c) levels were increasedin some non-diabetic pathological states especially Iron deficiency anemia. This study conducted on 52 non diabeticpregnant women sorrow from iron deficiency anemia and 30 non diabetic healthy pregnant women were enrolled to serveas a control group. The patient’s data released from National Hematology Center, Baghdad, Iraq for about five monthsand the required tests were examined under medical expert in this field in order to ensure the accuracy for thedemanding tests. The ages of patients were ranged from 20 to 45 years old. Our results showed a significant difference(P < 0.005) in case of Hba1C levels between iron deficiency anemia group and control group. Same results was found inall blood and biochemical tests which included in this study (serum ferritin, serum iron, serum total iron binding capacity,Hemoglobin level and Red blood cell count).
Keywords: Glycated hemoglobin, Non-diabetic, Pregnant.